Clinical outcomes in recurrent glioblastoma with bevacizumab therapy: An analysis of the literature. (October 2017) - Tipping, Matthew; Eickhoff, Jens; Ian Robins, H.
Highlights: Bevacizumab (BEV) is a common treatment for recurrent glioblastoma (r-GBM). Post BEV survival (OS) & progression free survival (PFS) are not well defined. Post BEV-OS & BEV-PFS were analyzed in r-GBM from 53 arms of 42 clinical trials. PFS = 4.38 M (95% CI 4.09–4.68); post-BEV-OS = 3.36 M (95% CI 3.12–3.66) [n = 2045]. These estimates provide a historical control for BEV-PFS & post BEV-OS. Abstract: Bevacizumab (BEV) is a common treatment for recurrent glioblastoma (GBM). After progression on BEV, there is no consensus on subsequent therapy, as multiple chemotherapy trials have failed to demonstrate discernible activity for salvage. A previous review (995 patients) estimated a progression free survival (PFS) on BEV of 4.2 months (SD ± 2.1) with an overall survival (OS) after progression on BEV at 3.8 months (SD ± 1). We endeavored to establish a more rigorous historical control, both as a benchmark for efficacy, and a prognostic tool for clinical practice. A comprehensive literature review was performed utilizing PubMed and societal presentation abstracts. A total 2388 patients from 53 arms of 42 studies were analyzed in three groups: 1) thirty-two studies in which survival post-BEV was determined by subtracting PFS from OS (2045 patients): PFS on BEV = 4.38 months (95% CI 4.09–4.68); OS post-BEV = 3.36 months (95% CI 3.12–3.66); 2) two studies (94 patients) in which OS post-BEV is reported: OS = 3.26 (95% CI 2.39–4.42); 3) eight studies of salvage therapy after progression on BEV (249 patients): of OS post-BEV = 4.46 months (95% CI 3.68–5.54). These estimates provide a firm historical control for PFS on BEV, as well as OS after disease progression on BEV therapy.